Social composition and spatial distribution of colonies in an expanding population of South American sea lions - Grandi, Maria Florencia (2008)
In northern Patagonia, South American sea lions (Otaria flavescens) are increasing in number after a depletive harvest. There has been an expansion of colonies with an increase in numbers of pups, and changes in social composition and spatial distribution. Using annual counts of 4 different age classes from 1972 to 2007, we found that new colonies change their social composition, transforming from haul-out sites to breeding sites while passing through mixed structures. From this pattern, we hypothesize that at dense breeding sites the shortage of space or the avoidance of intraspecific harassment promotes dispersal by 1st-time breeders to suitable sites nearby. Such mechanisms, along with philopatry and site fidelity, will promote the establishment of new breeding colonies nearer to existing breeding colonies than would be expected by chance. There was significant spatial clustering of new breeding colonies around the 7 focal (established) colonies. This spatial pattern was consistent through time. New breeding colonies were closer to focal colonies than are nonbreeding ones, suggesting a "spill-over" effect, where young individuals choose to breed near established breeders. The colonization mechanism we found suggests that potential areas for population expansion could be closer to areas where growing colonies already exist and highlights the importance of the juvenile age classes and the areas adjacent to colonies in the overall recovery of any population of pinnipeds.